2016
DOI: 10.1021/acs.jchemed.5b00710
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Instructional and Research Laboratories: Teaching Data Analysis Software Skills through the Manipulation of Original Research Data

Abstract: The gap between graduate research and introductory undergraduate teaching laboratories is often wide, but the development of teaching activities rooted within the research environment offers an opportunity for undergraduate students to have first-hand experience with research currently being conducted and for graduate students to develop communication and pedagogical skills. We describe the development, evaluation, and redesign of a Microsoft Excel-based activity where data analysis from contemporary research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Although the use of sample student data and research data for STEM laboratory classes has been demonstrated previously, , the instructors noticed two major challenges associated with the use of mined data. First, the data were difficult to understand when it was not originally collected by students themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Although the use of sample student data and research data for STEM laboratory classes has been demonstrated previously, , the instructors noticed two major challenges associated with the use of mined data. First, the data were difficult to understand when it was not originally collected by students themselves.…”
Section: Resultsmentioning
confidence: 99%
“…The learning cycle used in our activity was based on the cycle seen commonly in process oriented guided inquiry learning (POGIL) and involves a thorough exploration phase in which students are asked simple questions to draw their attention to key aspects of the model before building their knowledge with those observations [25]. Other instructional materials developed for the undergraduate biophysical chemistry course have focused on laboratory instruction [26][27][28][29]. Activities using the POGIL method, which incorporates the learning cycle similar to ours, have been developed for the biochemistry class [30][31][32], but none have been published specifically for the biophysical chemistry class to the best of our knowledge.…”
Section: Guided Inquirymentioning
confidence: 99%
“…Normally, statistical calculations and plotting are taught using spreadsheets. , For example, variances and means of two independent groups may be compared using the F test and t test, respectively. However, in recent years, programming software such as MATLAB, , Python, Octave, , and R project have been used for these purposes. Chemometric approaches such as machine learning, , multivariate calibration, and pattern recognition were taught using these programs.…”
Section: Introductionmentioning
confidence: 99%